Synthesis of Cyclopropanated 7-Oxabenzonorbornadienes - McKee, Mary; Haner, Jamie; Carlson, Emily; Tam, William (Synthesis, 2014)
Symmetrical and unsymmetrical 7-oxabenzonorbornadienes have been cyclopropanated using diazomethane gas under palladium catalysis. Good to excellent isolated yields (64–96%) of cyclopropanated oxabenzonorbornadienes were obtained, and excellent stereoselectivities were observed with exo-cyclopropanes as the only stereoisomeric products.
Keywords: 7-oxabenzonorbornadienes; cyclopropanation; diazo compounds; diastereoselectivity; palladium catalysis